Pengaruh Customer Intimacy, Price Fairness dan Customer Bonding Terhadap Customer Loyalty di Reni Salon Tales Ngadiluwih - Diah Ayu Fitrianingsih; Zaenul Muttaqien; Diana Ambarwati (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
This study aims to determine the effect of Customer Intimacy, Price Fairness, and Customer Bonding on Customer Loyalty at Reni Salon Tales Ngadiluwih. The selection of the research location is based on the consideration that Reni Salon is a beauty service business that has regular customers, but the level of customer loyalty cannot be measured precisely. The type of research used is quantitative research with an unknown population. The research sample amounted to 105 respondents who were determined by purposive sampling technique, namely the selection of samples based on certain criteria relevant to the research. The analysis techniques used include data quality testing, classical assumption testing, and multiple linear regression analysis with the help of Statistical Product and Service Solution (SPSS) version 25. This analysis is used to determine the influence of both partial and simultaneous between independent variables on the dependent variable. The results of the study indicate that partially, Customer Intimacy does not have a significant influence on Customer Loyalty. This indicates that personal closeness between the salon and customers is not yet a major factor in forming loyalty. Meanwhile, Price Fairness has a significant influence on Customer Loyalty, meaning that prices that are considered fair and appropriate by customers can increase their loyalty. Customer Bonding also had no significant effect on Customer Loyalty, indicating that emotional bonds or close customer relationships do not yet play a significant role. However, simultaneous test results show that all three variables—Customer Intimacy, Price Fairness, and Customer Bonding—jointly have a significant effect on Customer Loyalty. These findings suggest that price fairness plays the most critical role in enhancing customer loyalty compared to other factors. Therefore, Reni Salon management is advised to focus more on fair pricing strategies, along with efforts to strengthen closeness and bonds with customers.